'They can't be the buffer any longer': Front-line managers and class relations under white-collar lean production. (June 2014) - Carter, Bob; Danford, Andrew; Howcroft, Debra; Richardson, Helen; Smith, Andrew; Taylor, Phil
This article reasserts the value of the examination of class relations. It does so via a case study of tax-processing sites within HM Revenue and Customs, focusing on the changes wrought by the alterations to labour and supervisory processes implemented under the banner of 'lean production'. It concentrates on the transformation of front-line managers, as their tasks moved from those that required tax knowledge and team support to those that narrowed their work towards output monitoring and employee supervision. Following Carchedi, these changes are conceptualised as strengthening the function of capital performed by managers, and weakening their role within the labour process.